Between Symbolism and Strategy: Materiality Disclosure in Integrated Reporting across Indonesia and South Africa - Brigitta Aurelia Agatha; Ika Permatasari (Publikasi Inspirasi Indonesia, 2026)
Differences in the maturity of integrated reporting (IR) implementation across countries result in variations in materiality disclosure practices, which influence its role in corporate reporting. This study aims to conceptually analyze a comparison of materiality practices between South Africa and Indonesia. The method used is a qualitative approach with content analysis of the integrated reports of Nedbank and PT Garudafood Putra Putri Jaya. The results indicates that Nedbank applies materiality as a dynamic, continuous, and integrated process with the company’s strategy, risks, and performance. On the other hand, Garudafood has disclosed materiality systematically and transparently, yet it remains focused on reporting compliance and operational implementation with limited strategic aligment. These findings suggest that differences in practices lie not only in presentation methods but also in the role of materiality as a strategic tool.